Catolicismo, poder e controles no Oriente português (1557-1581): o caso da atuação eclesiástica de D. Gaspar de Leão, primeiro arcebispo de Goa (1557-1576) - Paula, Durval Saturnino Cardoso de (2015)
The aim of this research is to consider the history of the Portuguese Empire in the Orient during the XVI century by the ecclesiastical activity of D. Gaspar de Leão (1557-1576), the first archbishop of Goa. It focuses on the possible contradictions between the role played by this cleric and the tridentine reformation projects. Therefore, a series of writings by D. Gaspar de Leão and fisher documentation must be used as analytical tools. Specially, his book Desengano de Perdidos (1573) and the problems involving its censorship and prohibition by the Portuguese inquisition (1581) receive a particular attention